God, the best, and evil - Langtry, Bruce (Oxford : Oxford University Press, 2008)
Bruce Langtry examines implications of divine omnipotence omniscience, and perfect goodness for God's providence; the apparent fact that God could have created a better world than this one; and the problem of evil.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Providence and government of God -- Christianity; Theodicy; Good and evil